If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8r+4=8(r+2)-2r
We simplify the equation to the form, which is simple to understand
8r+4=8(r+2)-2r
Reorder the terms in parentheses
8r+4=+(+8r+16)-2r
Remove unnecessary parentheses
+8r+4=+8r+16-2r
We move all terms containing r to the left and all other terms to the right.
+8r-8r+2r=+16-4
We simplify left and right side of the equation.
+2r=+12
We divide both sides of the equation by 2 to get r.
r=6
| (3x-7)(4x-1)= | | 64y^4-x^3y^4= | | -5+16= | | 16+-1= | | P=4(162) | | 9(-5+4)=1+2x | | 3+8(2m+1)=16+15m | | 4d+3d-4d-5=2d | | 4x-22=4x+4 | | 5x+20=80 | | 10y=(3y+11) | | -10y-3y=-13 | | 7+7x-(-2x)+3=-4 | | 7+7x-(-2x)+3=4 | | 6z-3z=48 | | 21x^3+35x-9x^2-15=0 | | 20x-(3-5x)=47 | | 6y-y=35 | | a^2-5ab+6b^2=0 | | 18x^2-18x-108=0 | | 16x=8(2x+4) | | 5b+17-13b=7 | | 2(2x-5)+x=20 | | 7y-y=48 | | 96x^2+104x-8=0 | | 18+6m=0 | | 8x+3=-36x-32 | | 10x=5(2x+10) | | 8x+3=4-(9x-8) | | 6x+9=7-(2x-4) | | 4x-10=-14 | | -4x+5+9x-2=6 |